IMPROVEMENT OF HR PERFORMANCE BY A WORKING CONDITION APPROACH, AND WORK CONTENT WITH DISCIPLINE AS AN INTERVENTION VARIABLE (Case Study of The Department of Tourism Subo Suko Wono Sraten/Solo Raya) - Rumaningsih, Mrihrahayu; Sumarto, Laksono; Kasidin, Kasidin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
A good organization is an organization that seeks to improve its human resource capabilities, because it is a main factor for improving performance. The important things that need to be considered include; Safe, profitable and satisfactory working conditions also contribute to increasing employee motivation on work. In addition, work content is also no less important to measure employee performance.Original work content is the contents of the work or task given to employees and it is one of the supporting factors that provide smoothness of work motivation. The purpose of this study were to: (1) analyze and explain the effect of working conditions and work content on the discipline and employee performance (2) knowing and analyzing the mediation effect of discipline in the influence of work conditions and work content on employee performance. This research was conducted at the employees of the former Surakarta Residency Office of Surakarta, Boyolali, Sukoharjo, Wonogiri and Sragen, which are usually sacrificed (Subo Suko Wono Sraten or Solo Raya), each of which has 25 employees, so that the total total is 125 employees. Then each region was taken by 15 employees as respondents. The Path analysis is used to test the relationship between independent variables with the dependent variable mediated by the mediation variable. The results of the study found that (1) there is a positive influence and significant work conditions and work content on the discipline and employee performance (2) there is a direct influence that is better than working conditions and work content on employee performance than must be mediated by discipline. Keywords: working conditions, job content, discipline, performance, and path analysis.